Respuesta :

the answers are
7(x+3)
7(1+x)
7(x-7)

Answer:

6x + 18 → 6(x + 3)

6 + 6x → 6(1 + x)

6(x - 1) → 6x - 6

Step-by-step explanation:

What you do is use the distributive property on them. let's take the first one as an example. 6x + 18 = 6(x+3)

The distributive property bascially means that you multiply whatever number outside the parenthesis by what's inside of the parenthesis.

SO 6 · x = 6x and 6 · 3 = 18, all together, that equals 6x + 18. See how I distributed the 6 to both the number and the variable?